(untitled) (American International Journal of Agricultural Studies, 2024)
The need to analyze the changes that the effect of climate change brings on the income-generating activities of farmers in Enugu state necessitated this study. The study examined farmers’ socio-economic characteristics, described the perceived climate change effects, analyzed changes in income-generating activities, and evaluated the link between socio-economic factors and income-generating activities. Primary data were collected from 120 respondents using well-structured questionnaires. The data were analyzed using descriptive statistics and Pearson product-moment correlation. The results showed that the majority (73.3%) of the respondents were male farmers. Results of the study also showed that reduction in productivity (89.2%), change in farming pattern (77.5%), and soil degradation (65.0%) were the most perceived effects of climatic change among the respondents. The result also revealed strong negative change in income-generating activities in the areas of goat/sheep rearing (-33.4), fishing (-32.5), rabbit rearing (-15.0), and basket weaving (15.0), while petty trading (+23.4), hair barbing (+18.3) and food vending (+15.8) had strong positive change in the study area. The study revealed that socio-economic characteristics such as marital status, household size, and years of farming experience are correlated with positive income-generating activities. The study recommends that farmers should prioritize positive income-generating activities that correlate with their socio-economic characteristics. The study also recommends the implementation of crop rotation and organic manure as one of the ecological practices for climate change mitigation. JEL Classification Codes: Q00, O13.